Iterative technique for generating numerical on-axis holograms of an object on tilted planes using Rayleigh-Sommerfeld approximation (BISTUA Revista de la Facultad de Ciencias Básicas, 2021)
We present a new iterative technique based on successive field propagation using the Reyleigh-Sommerfeld (RS) approximation, to generate by computer the amplitude on-axis hologram of an object on a tilted plane. The technique was  validated doing optical and computational reconstruction of the hologram.
Keywords: Holography; Tilted Planes; Computer Generated Holograms